Analisis Faktor Hasil Penilaian Budi Pekerti - - Hadiwinarto (Jurnal Psikologi, 2014)
The purpose of this study was to describe the load factor of the assessment results on character education for high school students. The subjects were 545 second grade students. There were four instruments used, namely: cognitive aspect, affective aspect, behavioral aspect in the learning process and behavioral aspect outside the learning process. Each aspect contains nine indicators as factors. Data were analyzed with factor analysis technique and the models used were the Confirmatory Model of Principal Components Analysis with the varimak rotation method and Kaiser normalization. The results showed that each of these factors were statistically independent, not associated with other indicators. These findings reinforced the theories used in this study that character education loads indicators of dedication, conviction, honesty, discipline, tolerance, democracy, sense of belonging, gratitude and empathy. Statistically, each indicator obviously has four aspects of character. Therefore, assessment of manners that includes the aspects of cognitive, affective and behavior is a task that absolutely must be done. Keywords: character, factor analysis, cognitive, affective and behavioral